Vinegar: A potential source of healthy and functional food with special reference to sugarcane vinegar - Chen, Gan-Lin; Zheng, Feng-Jin; Lin, Bo; Yang, Yu-Xia; Fang, Xiao-Chun; Verma, Krishan K.; Yang, Li-Fang (Frontiers in Nutrition, 2023)
Vinegar is one of the most widely used acidic condiments. Nowadays, rapid advances have been made in the area of vinegar research. Different types of traditional vinegar are available around the globe and have many applications. It can be made either naturally, through alcoholic and then acetic fermentation, or artificially, in laboratories. Vinegar is the product of acetic acid fermentation of dilute alcoholic solutions. The first step is the production of ethanol from a carbohydrate source such as glucose which is carried out by yeasts. The second step is the oxidation of ethanol to acetic acid, carried out by acetic acid bacteria. Acetic acid bacteria are producers of certain foods and drinks, such as vinegar, but they can also spoil other products such as wine, beer, soft drinks, and fruits. Various renewable substrates are used for the efficient biological production of acetic acid, including agro and food, dairy, and kitchen wastes. Numerous reports of the health advantages associated with vinegar ingredients have been found. Fresh sugarcane juice was fermented with wine yeast and LB acetate bacteria to develop high-quality original sugarcane vinegar beverage. To facilitate this current study, the bibliometric analysis method was adopted to visualize the knowledge map of vinegar research based on literature data. The present review article will help scientists discern the dynamic era of vinegar research and highlight areas for future research.